(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Talent retention is a huge challenge the Information Technology Enabled Service sector faces, and it is a debatable issue. The attrition rate in the IT sector in India is 40-45 per cent. Observing the rate at which multinational companies are setting up subsidiaries in India, there is a possibility of greater and heavier demand for talent in multinational and domestic companies. This positive situation has suddenly increased the demand for skilled and talented employees. Employee job mobility was frequent in the Information Technology sector. Now, this trend is gradually spreading to other industries. Experts liken this to a virus because it signals that employers should focus on retaining talented and skilled staff, considering the costs of recruitment, selection, onboarding, training, and development. This shift has moved attention from simple personnel management to strategic human resources management, especially in IT, where the workforce is the key resource. Today, the main concern for human resources managers is keeping talented employees within the organization. This paper offers a comprehensive overview of employee retention and examines the main factors that influence an employee's likelihood of leaving the IT sector.